1964
DOI: 10.1111/j.1365-3180.1964.tb00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidal Effects on Certain Soil Microbial Activities in Some Brown Soils of Saskatchewan

Abstract: Amitrole, 2,3,6-TBA, 2,4-DB and di-allatc were applied at normal field rates to a loam soil in a preliminary study. The toxic effects, as measured by nitrification studies, persisted for 8 weeks after application. After a further 8 weeks this depressive effect was decreased.Residual effects were assayed hy measuring the nitrification rate of soils following the application ofthe same four herhicides at two rates to four different soils. The residual effects of amitroie. di-ailate, 2,3,6-TBA and 2.4-DB were ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1970
1970
1997
1997

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 15 publications
(4 reference statements)
1
3
0
Order By: Relevance
“…Thus, these results support the observations and hypotheses advanced by others who have worked with these and other herbicides (Chandra 1964;Tu and Bollen 1968;Grossbard 1985;Biederbeck et al 1987;Moorman 1989). For example, in a review paper, Moorman (1989) concluded that total microbial populations in soils are often unaffected, or only slightly affected, by pesticide applications, although individual species, such as cellulose decomposers, may be greatly affected.…”
Section: Carbon and Nitrogen Mineralizationsupporting
confidence: 90%
“…Thus, these results support the observations and hypotheses advanced by others who have worked with these and other herbicides (Chandra 1964;Tu and Bollen 1968;Grossbard 1985;Biederbeck et al 1987;Moorman 1989). For example, in a review paper, Moorman (1989) concluded that total microbial populations in soils are often unaffected, or only slightly affected, by pesticide applications, although individual species, such as cellulose decomposers, may be greatly affected.…”
Section: Carbon and Nitrogen Mineralizationsupporting
confidence: 90%
“…It is very unlikely that 850 ppm would be reduced to 100 ppm (see Table 2) during the perfusion period and the clear change in sensitivity finds its most logical explanation in a direct adaptation of the nitrifying organisms to herbicide toxicity. Chandra (1964), who also recorded inhibition of nitrification by 2,3,6-TBA, obtained evidence of a similar adaptation.…”
Section: Discussionmentioning
confidence: 65%
“…Dinoseb reduced respiration and plate counts of the saprophytic microHora for three months (GAMBLE et al 1952). The use of amitrole, 2,3,6-TBA, 2,4-D, and diallate resulted in reduced bacteria, actinomycete, and fungus counts (CHANDRA 1964). Paraquat increased the total number of fungi and percentage of penicillia but decreased mucors in one soil and not in another (Tu and BOLLEN 1968).…”
Section: D) Effect On Relationships Between Pathogens and Other Organmentioning
confidence: 96%